2013
DOI: 10.5897/ajb2012.3033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lactoperoxidase system on proteolysis and physicochemical changes in ultra high temperature milk during storage

Abstract: Indirect semi-skimmed ultra high temperature (UHT) milk was made from refrigerated milk preserved by the lactoperoxidase system (LPS). The effect of the LPS on the physicochemical and biochemical properties of UHT milk during storage period of 6 months at 30°C was assessed. The levels of soluble nitrogen at pH 4.6 and non protein nitrogen in all UHT milk samples increased during storage. However, control UHT milk, manufactured with refrigerated milk which LPS was not activated; showed the highest values (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Storage under 75 and 100/RT maintained SP concentration after 7 days ( p > 0.05), which tended to increase as the storage period increased, with a significant variation being observed from day 14 to 39 ( p < 0.05) of storage, under 75 and 100/RT, respectively. Especially, from day 39 until the end of the study, the SP concentration had a pronounce increase of almost 4- to 6-fold under 75 and 100/RT, respectively, which can be attributed to the enzymatic activity of proteases such as plasmin and microbial proteases . The SP increment in milk can occur in prolonged storage at RT, with Olfa et al reporting an increase of 140% from day 0 to 60 days at 30 °C in the SP content of UHT milk, possibly as a result of thermoresistant microbial proteases (mainly fromPseudomonas spp.)…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Storage under 75 and 100/RT maintained SP concentration after 7 days ( p > 0.05), which tended to increase as the storage period increased, with a significant variation being observed from day 14 to 39 ( p < 0.05) of storage, under 75 and 100/RT, respectively. Especially, from day 39 until the end of the study, the SP concentration had a pronounce increase of almost 4- to 6-fold under 75 and 100/RT, respectively, which can be attributed to the enzymatic activity of proteases such as plasmin and microbial proteases . The SP increment in milk can occur in prolonged storage at RT, with Olfa et al reporting an increase of 140% from day 0 to 60 days at 30 °C in the SP content of UHT milk, possibly as a result of thermoresistant microbial proteases (mainly fromPseudomonas spp.)…”
Section: Resultsmentioning
confidence: 90%
“…This enzyme might be more susceptible to the changes observed under these storage conditions, AP/RT, AP/RF, and 50/RT, namely, high microbial activity, decrease in pH, and increase in acidity, which all together can promote LPO denaturation and/or reduce its activity. 22 Storage under 75 and 100/RT presented overall a much better maintenance in LPO residual activity throughout storage, compared to the other storage conditions performed. At day 7, both storage conditions presented an increased LPO activity, compared to the initial one, to values around 113% (p < 0.05) and 123% (p < 0.05) for 75 and 100 MPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant change was observed in the control-raw milk. The results indicate that activation of the lactoperoxidase system occurs within the first three h. A study reported that activation of the lactoperoxidase system in raw milk is quite effective against psychrotroph bacteria, since it increases the shelf life of cold stored milk for several days [26] . As reported by another study, the initial psychrotroph bacterial load in the raw cow milk was 5.5×10 3 /mL, and in the activated group, it reduced to 2.6×10 6 /mL on 6 th day.…”
Section: Discussionmentioning
confidence: 97%